(3GdRgQIs - (3GdXGgQj , eMeO Hf OGhO Hf Ydj Hf Nda, CHh HcQ,J (B297 (3g` s
(3ChdgG (B:s
(3PcQ eG jLYd ef GdGSJHWGA ebOeg Hjf GdgLGA s
(3BNQgG (B:s
(3HJhQI hBNQ GehLhO ajg(B: (3GYWi eGLGA ai GdTYQ ef eSJhQ? dGjage SGeY EdG HJaSjQ bhd Hi JeGe(B! (3CYWi HcdJG jOjg MJdG bjd dg gPG GHhoOda GdYLdi bO OdaG s
(3GdfSNI HgG MhGTs
(3YdjgG Jedc GdCH CfSJGS eGQi GdcQedi SfI (B1933s
(3fSNI fajSI NRGFfjI ? cJHJ ddSdWGf CHj GdaOG ESeGYjd Hf Gdedc GdYGOd Sja GdOjf CHj HcQ Hf CjhHs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs